2022
DOI: 10.3390/antiox11081515
|View full text |Cite
|
Sign up to set email alerts
|

The Microalgal Diatoxanthin Inflects the Cytokine Storm in SARS-CoV-2 Stimulated ACE2 Overexpressing Lung Cells

Abstract: Contact between SARS-CoV-2 and human lung cells involves the viral spike protein and the human angiotensin-converting enzyme 2 (ACE2) receptor on epithelial cells, the latter being strongly involved in the regulation of inflammation as well as blood pressure homeostasis. SARS-CoV-2 infection is characterized by a strong inflammatory response defined as a “cytokine storm”. Among recent therapeutic approaches against SARS-CoV-2 targeting the dramatic inflammatory reaction, some natural products are promising. Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…We have recently demonstrated that diatoxanthin, a carotenoid derived by marine diatoms, significantly upregulates IL-10 production, increases ACE2 activity, exerts an immunomodulant effect by up-regulating antiviral defense genes and by strongly inhibiting spike-induced inflammatory response in a lung cell line. Diatoxanthin, exclusively found in marine environment, decreases the release of pro-inflammatory mediators responsible for cytokines storm in SARS-COV2 disease, supporting the therapeutic potential of marine-derived bioactive compounds against COVID-19 ( 290 ).…”
Section: Natural Bioactive Compounds Influencing Il-10 Productionmentioning
confidence: 91%
“…We have recently demonstrated that diatoxanthin, a carotenoid derived by marine diatoms, significantly upregulates IL-10 production, increases ACE2 activity, exerts an immunomodulant effect by up-regulating antiviral defense genes and by strongly inhibiting spike-induced inflammatory response in a lung cell line. Diatoxanthin, exclusively found in marine environment, decreases the release of pro-inflammatory mediators responsible for cytokines storm in SARS-COV2 disease, supporting the therapeutic potential of marine-derived bioactive compounds against COVID-19 ( 290 ).…”
Section: Natural Bioactive Compounds Influencing Il-10 Productionmentioning
confidence: 91%
“…Although further studies are needed to elucidate the underlying mechanism, these results provide useful information on the application of these marine carotenoids for the treatment and prevention of COVID-19. Their possible application as a new therapeutic agent in the treatment and/or prevention of the severe inflammatory syndrome related to SARS-CoV-2 infection has been further supported by the in silico identification and in vitro validation of the binding between xanthophyll diatoxanthin (Dt) and ACE2 protein [ 133 ].…”
Section: In Silico Analysis and Validation To Discover Antioxidant Pr...mentioning
confidence: 99%
“…In algae cells, Fx has a main role in light harvesting, and low light (LL) conditions increase the production of this carotenoid [10,14,15]. Recent research has highlighted the pronounced bioactivity of another marine carotenoid, diatoxanthin (Dtx), outperforming commercially available carotenoids as potential disease preventing agents [16][17][18][19]. Antioxidant and anti-inflammatory abilities have been reported where Dtx has lowered the production of reactive oxygen species (ROS) and pro-inflammatory cytokines in vitro [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has highlighted the pronounced bioactivity of another marine carotenoid, diatoxanthin (Dtx), outperforming commercially available carotenoids as potential disease preventing agents [16][17][18][19]. Antioxidant and anti-inflammatory abilities have been reported where Dtx has lowered the production of reactive oxygen species (ROS) and pro-inflammatory cytokines in vitro [16][17][18]. Dtx has also been suggested as a potential therapeutic agent in the treatment and/or prevention of the severe inflammatory syndrome related to SARSCoV-2 infection [18].…”
Section: Introductionmentioning
confidence: 99%